2019
DOI: 10.1007/s00340-019-7342-5
|View full text |Cite
|
Sign up to set email alerts
|

A Faraday laser operating on Cs 852 nm transition

Abstract: We demonstrate a Faraday laser at Cs-D2 resonance line 852 nm using a Cs Faraday optical filter as frequency-selecting element. In contrast to typical diode laser with high stability of the emission frequency by additional control systems, our Faraday laser offers stable output frequency exactly set by the peak transmission frequency of the Cs 852 nm Faraday optical filter. The system works stably over a range of laser diode (LD) current from 60 to 130 mA and the LD temperature from 14 to 35 • C, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Examples of the former include filtering of frequency-degenerate photon pairs [213]; filtering of Mollow-triplet sidebands [214]; recording atomic spectra with single-molecule light sources [215]; free-space optical communications [216] and quantum key distribution [217]. Examples of the latter include Faraday lasers [64,[218][219][220][221]; Doppler velocimetry [222]; atmospheric LIDAR [223][224][225][226][227][228]; simultaneous atmospheric wind and temperature measurement [229]; and discerning rocket plumes from sunglints [230]. In addition, the same principle of achieving large optical rotation with minimal absorption in the vicinity of an atomic resonance has been used to realise different photonic devices, such as dichroic beam splitters (BSs) [59,231], and compact OIs [58].…”
Section: Narrowband Atomic Line Filtersmentioning
confidence: 99%
“…Examples of the former include filtering of frequency-degenerate photon pairs [213]; filtering of Mollow-triplet sidebands [214]; recording atomic spectra with single-molecule light sources [215]; free-space optical communications [216] and quantum key distribution [217]. Examples of the latter include Faraday lasers [64,[218][219][220][221]; Doppler velocimetry [222]; atmospheric LIDAR [223][224][225][226][227][228]; simultaneous atmospheric wind and temperature measurement [229]; and discerning rocket plumes from sunglints [230]. In addition, the same principle of achieving large optical rotation with minimal absorption in the vicinity of an atomic resonance has been used to realise different photonic devices, such as dichroic beam splitters (BSs) [59,231], and compact OIs [58].…”
Section: Narrowband Atomic Line Filtersmentioning
confidence: 99%
“…4 a). We can achieve any value of field between the maximum and 1.80 (8) kG; examples are shown in Fig. 5 b) and c).…”
Section: Resultsmentioning
confidence: 99%
“…MOFs find a wide range of applications in other disciplines including e.g. quantum key distribution [4]; optical isolators [5]; atmospheric LI-DAR [6,7]; and laser frequency stabilization [8,9]. In certain cases there is the need to produce large, uniform magnetic fields (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The Faraday laser [17]- [19], which is composed of an antireflection-coated laser diode (ARLD) as gain medium, a FADOF as frequency-selection element, and a high-reflectivity mirror for optical feedback, can stably operate at atomic Doppler broadened line with frequency being immune to the current and temperature fluctuation of laser diode (LD). It has been confirmed that the wavelength fluctuation of Faraday laser can achieve no more than ±2 pm within 48 hours [20]. Compared with the typical external-cavity diode lasers (ECDLs) utilizing interference filters (IFs) [21], [22], gratings [23], [24], or Fabry-P érot etalons [25], [26] as mode-selection elements, the Faraday lasers take advantage of the narrow-bandwidth atomic filter for frequency selection with frequency being set by the peak transmission frequency of FADOF.…”
Section: Introductionmentioning
confidence: 83%
“…Previous researches on Faraday lasers exclusively focused on the single-frequency operation [16], [18], [20]. However, the dual-frequency (DF) laser is of great importance in the fields like frequency stabilization and high-resolution spectroscopy.…”
Section: Introductionmentioning
confidence: 99%